Generating an Equation to Predict Post- Farrow Maternal Weight in Multiple Parity Sows - L. L. Thomas; S. S. Dritz; R. D. Goodband; M. D. Tokach; J. M. DeRouchey; J. C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2016)
ost-farrow maternal weight is required when partitioning maternal and fetal weight gains throughout gestation. Equations were developed from the analysis of 150 females (Line 1050, PIC, Hendersonville, TN) to predict the weight of conceptus by difference of pre- and post-farrowing weight change in multi-parity sows. Females were individually weighed as they were moved into the farrowing house at d 110 to 112 of gestation and again at 12 to 24 h after farrowing. Data were divided into 4 groups: (1) parity 1 sows; (2) parity 2 sows; (3) parity 3 sows; and (4) parity 4+ sows. Each group tested 3 predictor variables: pre-farrow weight, total born, and difference in days between the pre- and post-farrow weights. Prediction equations were then developed using models with significant terms based on the Bayesian Information Criterion (BIC). The optimum equations to predict maternal body weight were similar for all parities except for the intercept (b) and can be described as: Post-farrow maternal body weight (lb) = b + (0.897 × pre-farrow BW, lb) - (1.118 × total born, n) + (6.87 × days pre to post-farrow, d) Where the intercept (b) for parities 1, 2, 3, and 4+ were -5.93, 5.15, 11.90, and 32.31, respectively. The prediction equations were then used to estimate post-farrow maternal BW using 332 mixed parity sows (PIC 1050). Pre-farrow weights were taken on d 113 of gestation and maternal BW was taken within 24 h of farrowing. On average, the predicted postfarrow maternal BW was overestimated by 3.3 lb of the actual. Management practices differed in how females were fed from the validation experiment, possibly contributing to the overestimating of post-farrow maternal BW. This indicates that further evaluation of the equation is needed to see if the difference is due to litter size, parity distribution, or feeding management practices.
Keywords: sows; post-farrow maternal weight